Engaging reader response questioning prompts in literature lessons: a case study of secondary school in Shah Alam / Faridatul Bariza Md Nasir - Md Nasir, Faridatul Bariza (2013)
This research aimed to investigate the dominant type of questioning prompts used by teachers specifically whilst teaching English Literature in ESL literature classrooms. There were five research questions examined: i) What is the most dominant type of questioning prompts used in ESL classrooms during literature lessons as perceived by the students?; ii) What is the most dominant type of questioning prompts used in ESL classrooms during literature lessons as perceived by the teachers?; iii) What types of questioning prompts do teachers use during ESL literature class?; iv) How do teachers feel about students’ readiness in handling the four types of question?; and v) What techniques do teachers use to assess their students’ understanding of literature in the classroom?. This study employed a case study research design with a total number of 204 students and three English language teachers from SMKBJU, Shah Alam. The instruments employed were questionnaires and semi-structured interviews. Form four students answered the questionnaires while the teachers participated in the interview sessions. The findings of the questionnaires revealed that the students agreed interpretive questioning prompts were mostly used by their teachers during their ESL literature classes. This finding is also aligned with the teachers interviews as all the teachers agreed they use interpretive prompts most of the time in the classroom. All three teachers adapted all of the four questioning prompts but they did not cover all in an equal manner as they are restrained by the standardized examination format and time constraints. The teachers feel that students with high proficiency in the language are able to cope with the critical questioning prompts otherwise the students will have difficulties. Lastly, the techniques teachers use to assess their students is through questioning, quizzes, tests and homework. The findings hoped to provide an input in towards giving exposure to other teachers on the different types of questioning prompts during ESL classroom so the teachers are not confined to asking the same type of questions.